An investigation into the role of alcohol in self-harm in rural Sri Lanka: a protocol for a multimethod, qualitative study. Issue 10 (7th October 2014) - Sørensen, Jane Brandt; Rheinländer, Thilde; Sørensen, Birgitte Refslund; Pearson, Melissa; Agampodi, Thilini; Siribaddana, Sisira; Konradsen, Flemming
Abstract : Introduction: Sri Lanka has one of the highest suicide and self-harm rates in the world and although alcohol has been found to be a risk factor for self-harm in Sri Lanka, we know little about the connection between the two. This paper comprises a protocol for a qualitative study investigating alcohol's role in self-harm in rural Sri Lanka at three levels: the individual, community and policy level. The analysis will bring new understanding of the link between alcohol and self-harm in Sri Lanka, drawing on structural, cultural and social concepts. It will equip researchers, health systems and policy makers with vital information for developing strategies to address alcohol-related problems as they relate to self-harm. Methods and analysis: To capture the complexity of the link between alcohol and self-harm in the Anuradhapura district in the North Central Province in Sri Lanka, qualitative methods will be utilised. Specifically, the data will consist of serial narrative life-story interviews with up to 20 individuals who have non-fatally self-harmed and where alcohol directly or indirectly was involved in the incidence as well as with their significant others; observations in communities and families; six focus group discussions with community members; and key-informant interviews with 15–25 stakeholders who have a stake in alcohol distribution, marketing, policies, prevention and treatment as they relate to self-harm. Ethics and dissemination: The study has received ethical approval from the Ethical Review Committee of the Faculty of Medicine and Allied Sciences, Rajarata University of Sri Lanka. A sensitive data collection technique will be used and ethical issues will be considered throughout the study. Results: The results will be disseminated in scientific peer-reviewed articles in collaboration with Sri Lankan and other international research partners.